(untitled) (International Journal of Food and Nutritional Sciences, 2023)
The study was conducted at Karguaji Research farm, Institute of Agricultural Sciences, Bundelkhand University, Jhansi, in Rabi 2020, aiming to estimate genetic parameters such as coefficient of variation, heritability, and genetic advance as percentage of mean for seed yield and its components for wheat genotypes. The results showed maximum variability in plant height and lowest in flag leaf width. The coefficient of variation was found to be higher than the genetic coefficient of variation for most traits except for three, which were not influenced by the environment. High heritability and genetic advance were observed for traits like 1000 seed weight, leaf sheath length, plant height, flag leaf width, number of seed per spike, harvest index, flag leaf length, biological yield per plant, number of tillers per plant, and number of spike per plant. This suggests that heritability is likely due to additive gene effects and selection may be effective. However, high heritability and low genetic advance were observed for the single trait, days to maturity, indicating a preference for non-additive gene action.